Design and development of a spiritual care competency framework for pre-registration nurses and midwives: A modified Delphi study. (August 2019) - Attard, Josephine; Ross, Linda; Weeks, Keith W.
Abstract: This is the second of two papers reporting the development of a spiritual care competency framework for pre-registration nurses and midwives as part of a PhD study using an embedded sequential mixed methods eclectic research design. The first paper outlines how 116 competency items were generated from an in-depth review of international literature, and offers a theoretical model to underpin development of the Framework. Aim: This paper reports how the Framework was developed. Method/Results: Five focus groups were held with stakeholders in Malta (chaplains/spiritual leaders, undergraduate nursing/midwifery educators, qualified nurses/midwives, parents/carers, patients/clients) to ensure that aspects of spirituality/spiritual care important to them, but not identified in the literature review, were included in the Framework. The resulting 55 competencies in seven domains formed the Delphi Questionnaire which was validated using a two round modified Delphi method involving experts from Malta. The final seven domain 54 item Framework demonstrated good to strong internal consistency, stability and a good fit with a six factor model. Conclusion: The Framework's greatest immediate contribution is in its ability to inform undergraduate nursing/midwifery spiritual care curriculum design and delivery. Further development of the Framework could assist in student selection ensuring that the 'art' of nursing/midwifery has parity with the 'science'. Highlights: This is the first pre-registration Spiritual Care Competency Framework for nurses/midwives. It was developed using a rigorous embedded sequential mixed methods eclectic research design. The Framework is informing design/delivery of spiritula care education programmes across Europe